2019
DOI: 10.1111/acv.12536
|View full text |Cite
|
Sign up to set email alerts
|

Energetics suggest cause for even further conservation concern for Temminck’s ground pangolin

Abstract: Conservation of rare and declining species requires reliable information about life‐history traits and population growth characteristics. Unfortunately, long‐term studies necessary to obtain such data are often difficult or impossible for species of concern. In such cases, data that can be collected during limited capture events can serve as valuable proxies. We measured metabolic characteristics of Temminck’s ground pangolin Smutsia temminckii because metabolic traits provide clues about relative gestation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Second, once expended, their energy reserves are not easily replenished, as prey availability in winter is limited as low ambient temperature reduces prey activity and abundance [1,[4][5][6]. Therefore, temperate bats reduce their energetic costs in winter by engaging in periodic bouts of torpor, a physiological state characterized by low body temperature and metabolic rate, for prolonged periods of time [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Second, once expended, their energy reserves are not easily replenished, as prey availability in winter is limited as low ambient temperature reduces prey activity and abundance [1,[4][5][6]. Therefore, temperate bats reduce their energetic costs in winter by engaging in periodic bouts of torpor, a physiological state characterized by low body temperature and metabolic rate, for prolonged periods of time [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The body temperature of pangolins has been found to be lower than that of other placental mammals of similar size, likely reflecting their low metabolic rate ( McNab, 1984 ; Griebeler and Werner, 2016 ; Boyles et al, 2019 ). Pangolins in our study, however, had mean body temperatures that were higher compared with those measured previously for Temminck’s pangolins in captivity (32–34°C; Boyles et al, 2019 ; Wicker et al, 2020 ) and for one animal in the wild (32–35°C; Pietersen, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The body temperature of pangolins has been found to be lower than that of other placental mammals of similar size, likely reflecting their low metabolic rate ( McNab, 1984 ; Griebeler and Werner, 2016 ; Boyles et al, 2019 ). Pangolins in our study, however, had mean body temperatures that were higher compared with those measured previously for Temminck’s pangolins in captivity (32–34°C; Boyles et al, 2019 ; Wicker et al, 2020 ) and for one animal in the wild (32–35°C; Pietersen, 2013 ). The highest (absolute maximum) body temperature (38.2°C) we measured was higher than the maximum body temperatures reported previously for any pangolin species in captivity (33.9–37.8°C, Jones, 1973 ; McNab, 1984 ; Heath and Hammel , 1986 ; Heath, 1987 ; Boyles et al, 2019 ; Challender et al, 2020 ; Yu et al, 2021 ) and almost 3°C higher than that previously reported for a wild Temminck’s pangolin (35.4°C), measured across 34 days in winter ( Pietersen, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although global trends in female fertility rates have been declining over the past few decades, , female reproductive disorders are generally understudied in the scientific community. Many factors influence the continuous decline of female reproductive health, and the role of environmental exposure in the development of female reproductive disorders warrants further attention …”
Section: Introductionmentioning
confidence: 99%
“…Many factors influence the continuous decline of female reproductive health, and the role of environmental exposure in the development of female reproductive disorders warrants further attention. 5 Phthalates, a class of endocrine-disrupting compounds (EDCs), are derived from the esterification of phthalic acids. 6 They make up a group of chemicals used as plasticizers and flavor enhancers and are widely used in food packaging, personal care, and industrial products.…”
Section: Introductionmentioning
confidence: 99%